Plasma elaidic acid level is associated with periodontal health in American adults: A cross-sectional study - Jiaxin, Hu; Zhu, Chen; Jing, Yang; Qianhui, Shi; Fuqian, Jin; Qiyuan, Pang; Yi, Luo; Jukun, Song (Frontiers in Nutrition, 2022)
Background: Whether there is an association between TFAs and periodontitis is unclear. The purpose of this study was to investigate the relationship between moderate/severe periodontitis and plasma level of elaidic acid, a major trans-fatty acid component, in American adults. Methods: The National Health and Nutrition Examination Survey years 2009-2010 were used to screen a total of 1610 people. The independent variable of interest is plasma elaidic acid level, the dependent variable is periodontitis, and the covariates include socio-demographic variables, lifestyle variables, systemic diseases, etc. The distribution of variables in the covariate differences between the different independent groups according to tertile was investigated using a multiple linear regression model. To examine the association between plasma elaidic acid levels and moderate/severe periodontitis, three models were used; Results: Multiple logistic regression analysis showed a significant association between plasma elaidic acid level and moderate/severe periodontitis after adjustment for potential confounders (OR = 1.021, 95%CI:1.004-1.039, P=0.01394). Subjects with the highest tertile of plasma elaidic acid levels were 51.9% more likely to have periodontitis compared with subjects with the lowest tertile of plasma elaidic acid levels (OR = 1.519, 95% CI: 1.136-2.030, P = 0.00477). No possible sources of heterogeneity were identified in the subgroup analyses. Conclusion: Plasma elaidic acid levels are associated with periodontal disease in American adults.